Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1177/096032710003200404
|View full text |Cite
|
Sign up to set email alerts
|

Preferred luminous conditions in open-plan offices: research and practice recommendations

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 20 publications
5
80
1
Order By: Relevance
“…The average preferred illuminance level for long-term office work was 648 lx with FL lighting and 517 lx with LED lighting. The preferred illuminances were slightly higher than in some previous findings [104]- [106] but close to those found in [107].…”
Section: User Adjusted Illuminance Level and Cct Preferencessupporting
confidence: 78%
“…The average preferred illuminance level for long-term office work was 648 lx with FL lighting and 517 lx with LED lighting. The preferred illuminances were slightly higher than in some previous findings [104]- [106] but close to those found in [107].…”
Section: User Adjusted Illuminance Level and Cct Preferencessupporting
confidence: 78%
“…The relationship between gender and light quality (satisfaction with office lighting and task lighting) was identified in the field study by Aries et al [16]. Knez and Enmarker [31] reported that lighting was perceived significantly differently by females compared to males, but gender was unrelated to lighting preferences [41] or the effects of lighting on cognitive task performance [18]. In open-plan offices, environmental conditions such as office layout planning, privacy and lighting were evaluated more negatively by female workers compared to males [44].…”
Section: Kim J De Dear R Cândido C Zhang H Arens E 2013 Gender mentioning
confidence: 99%
“…We are also experienced in conducting lighting experiments in real spaces of this kind. We used a photograph of a cubicle in the same physical space as that studied by Veitch & Newsham [15][16] because their results could then be compared to the results of this study.…”
Section: The Imagementioning
confidence: 99%
“…All of the studies we refer to in this section excluded daylight and derived preferences for electric lighting only, analogous with our study. Veitch and Newsham 16 conducted a study in the same laboratory space in which the photograph used in this study was taken. Participants had dimmable control over three lighting circuits (one indirect and two direct) as well as on-off control over an undershelf task light.…”
Section: Are Preferred Luminances and Ratios The Same As Those Derivementioning
confidence: 99%
See 1 more Smart Citation